2009
DOI: 10.1007/s00404-009-1010-7
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar coagulation with the BiClamp® forceps versus conventional suture ligation: a multicenter randomized controlled trial in 175 vaginal hysterectomy patients

Abstract: The BiClamp procedure proved superior or similar to conventional ligation, particularly with regard to intraoperative blood loss, operating time and postoperative pain, although statistical significance was not attained for postoperative pain. Moreover, BVS was easier to use and more cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 19 publications
5
33
1
3
Order By: Relevance
“…Bogani et al pointed out that the patient BMI is directly proportional to the rate of complications due to hysterectomy. The higher intraoperative complication rates in our study and control groups compared with those reported in previously published studies could be explained by these factors [9,12,[14][15][16][17].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Bogani et al pointed out that the patient BMI is directly proportional to the rate of complications due to hysterectomy. The higher intraoperative complication rates in our study and control groups compared with those reported in previously published studies could be explained by these factors [9,12,[14][15][16][17].…”
Section: Discussionsupporting
confidence: 50%
“…Accordingly, a few authors suggested the use of advanced electrosurgical instruments that provide the ability to rapidly and sequentially seal vessels and coagulate and transect pedicles with a tool manipulated by one hand. Previous studies showed such instruments adapted to vaginal surgery from laparoscopic practice were suitable alternatives to conventional suturing techniques and had similar safety profiles [7,12,13]. To our knowledge, no studies have yet compared the surgery-related outcomes of EBVS system and conventional suture ligation technique only focusing on the morbidly obese patients undergoing VH.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in hospital stay was also seen by Clave et al (6 days v/s1 day), Ding et al (1.2 vs 3 days), Lewy et al (1 vs 3 days) and Zubke et al (6.6 vs 7.4 days). 16,18,20,23 Cronje and de Coning did not find a significant difference. 19 We conducted present study on a mixed group of patients with various indications, with different surgical difficulties in different groups.…”
Section: Discussionmentioning
confidence: 76%
“…16,21,22 Relatively more number of women had blood loss >100 ml in suture group i.e. 34 out of 86 versus 9 out of 88 patients in the sealer group in the study by Zubke et al 20 Even though most studies noted this difference in blood loss, studies of Hefni et al and Cronje and de Coning did not find any significant difference in blood loss between the two group of patients. 17,19 We evaluated post-operative pain on Visual Analogue Scale on a score of 1-10.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation